2000
DOI: 10.1038/sj.onc.1203823
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of Sp1-mediated transcriptional activation of the human DNA polymerase β promoter

Abstract: In the present studies, we have examined the e ect of Sp1 on the activation of the human DNA polymerase b (b-pol), a TATA-less promoter. A HeLa cell nuclear extract (NE) based in vitro runo transcription system of core b-pol promoter human DNA (pbP8) three-step kinetic model of transcription initiation were used to describe the kinetic e ect of Sp1. The results showed that distal Sp1-binding sites in the core b-pol promoter are important for transcriptional activation of the pbP8 promoter. A detailed kinetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Wilson et al further identified SP1 and CRE sites within this region [23]. Sp1 sites in the human core β-POL promoter have been shown to be involved in the transcriptional activation of the TATA less promoter [49]. The CRE site, the general binding site for ATF-1, CREB-1, CREM-1 and AP-1, has been shown to be involved in the expression of human β-POL during basal conditions and during stress [2426,50].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al further identified SP1 and CRE sites within this region [23]. Sp1 sites in the human core β-POL promoter have been shown to be involved in the transcriptional activation of the TATA less promoter [49]. The CRE site, the general binding site for ATF-1, CREB-1, CREM-1 and AP-1, has been shown to be involved in the expression of human β-POL during basal conditions and during stress [2426,50].…”
Section: Discussionmentioning
confidence: 99%
“…This upregulation requires the presence of the specific cAMP response element (CRE) in the promoter of the Pol β gene (9,10). It has also been shown that the Pol β promoter contains a binding site for the transcription factor SP1 (11). Although regulation at the transcription level is apparent, expression of the Pol β transcripts might also be controlled at the post-transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…TEL is one of a subset of the ETS family of transcription factors that contains a conserved N‐terminal domain which has been variously referred to as the pointed (PNT) domain, based on homology to the Drosophila ETS‐protein pointed , the N‐terminal conserved domain (NCR), or the helix‐loop‐helix domain, based on weak homology to the basic helix‐loop‐helix domain found in transcription factors such as myc and myo‐D (Wasylyk et al ., 1993). The PNT domain was shown to be important for transcriptional activity despite the lack of DNA contact, but no other function was known prior to the cloning of the TEL/PDGFRβ fusion gene (Rao et al ., 1993). Analysis of the TEL fusion proteins in the context of the PNT domain has provided evidence that this domain acts as a self association domain of functional importance.…”
Section: Introductionmentioning
confidence: 99%